The effect of oil palm trunk particles and composite density on the physical and mechanical properties of rigid polyurethane foam composite. Issue 1 (November 2021) - Munawar, S S; Widyanto, C D; Hutahean, L S; Purnomo, D; Subiyanto, B; Ismadi,; Syahrir, A; Akbar, F; Kosasih, D P
Abstract: The oil palm trunk (OPT) particle was used as a filler for the manufacture of rigid polyurethane foam composites (RPUFC). The purpose of this research is to investigate the effect of OPT particle content and variation of composite density on the physical and mechanical properties of RPUFC. The RPUFC was created with five different volume fractions of OPT particles (0, 2.5, 5, 7.5, 10 wt%) and three different composite densities (40, 50, 60 kg/m 3 ). The OPT particles, polyols, and isocyanate were mixed, poured and formed in a closed mold. The moisture content (MC), water absorption (WA), compressive strength (CS), screw withdrawal (SW), and internal bonding strength (IB) properties were determined according to JIS A 5908-2003. The flexural strength (FS) properties were determined according to ASTM D790. The physical properties (MC, WA) were increased with increasing OPT particles in the RPUFC. The RPUFC with 2.5% OPT particle was higher in modulus of rupture, modulus of young and CS values compared to RPUFC control. The IB and SW values were increased when 2.5% OPT particles were added to RPUFC. The best PURFCs were produced with the addition of 2.5% particles at a density of 50 and 60 kg/m 3 .